2013
DOI: 10.1155/2013/612458
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses Associated with Daily Walking in Subacute Stroke

Abstract: Despite the importance of regaining independent ambulation after stroke, the amount of daily walking completed during in-patient rehabilitation is low. The purpose of this study is to determine if (1) walking-related heart rate responses reached the minimum intensity necessary for therapeutic aerobic exercise (40%–60% heart rate reserve) or (2) heart rate responses during bouts of walking revealed excessive workload that may limit walking (>80% heart rate reserve). Eight individuals with subacute stroke attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
1
33
0
1
Order By: Relevance
“…Similar duration and intensity of routine physiotherapy were found by previous studies [3][4][5]. For example, maximum average HRR achieved in the present study (32%) was similar to 35% reported by Kuys et al [4] for stepping.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar duration and intensity of routine physiotherapy were found by previous studies [3][4][5]. For example, maximum average HRR achieved in the present study (32%) was similar to 35% reported by Kuys et al [4] for stepping.…”
Section: Discussionsupporting
confidence: 91%
“…There are now four international studies [3][4][5], including the present one (Canada, Australia, Brazil) that informed us that physiotherapists do not do it. Why?…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations